Arterial and Cardiac Remodeling Associated With Extra Weight Gain in an Isolated Abdominal Obesity Cohort - Mandry, Damien; Girerd, Nicolas; Lamiral, Zohra; Huttin, Olivier; Filippetti, Laura; Micard, Emilien; Ncho Mottoh, Marie-Paule Bernadette; Böhme, Philip; Chemla, Denis; Zannad, Faïez; Rossignol, Patrick; Marie, Pierre-Yves (Frontiers in Cardiovascular Medicine, 2021)
Introduction: This study aims to assess the changes in cardiovascular remodeling attributable to bodyweight gain in a middle-aged abdominal obesity cohort. A remodeling worsening might explain the increase in cardiovascular risk associated with a dynamic of weight gain. Methods: Seventy-five middle-aged subjects (56 ± 5 years, 38 women) with abdominal obesity and no known cardiovascular disease underwent MRI-based examinations at baseline and at a 6.1 ± 1.2-year follow-up to monitor cardiovascular remodeling and hemodynamic variables, most notably the effective arterial elastance (Ea). Ea is a proxy of the arterial load that must be overcome during left ventricular (LV) ejection, with increased EA resulting in concentric LV remodeling. Results: Sixteen obese subjects had significant weight gain (>7%) during follow-up (WG+), whereas the 59 other individuals did not (WG–). WG+ and WG– exhibited significant differences in the baseline to follow-up evolutions of several hemodynamic parameters, notably diastolic and mean blood pressures (for mean blood pressure, WG+: +9.3 ± 10.9 mmHg vs. WG–: +1.7 ± 11.8 mmHg, p = 0.022), heart rate (WG+: +0.6 ± 9.4 min−1 vs. −8.9 ± 11.5 min−1, p = 0.003), LV concentric remodeling index (WG: +0.08 ± 0.16 g.mL−1 vs. WG−: −0.02 ± 0.13 g.mL−1, p = 0.018) and Ea (WG+: +0.20 ± 0.28 mL mmHg−1 vs. WG−: +0.01 ± 0.30 mL mmHg−1, p = 0.021). The evolution of the LV concentric remodeling index and Ea were also strongly correlated in the overall obese population (p < 0.001, R2 = 0.31). Conclusions: A weight gain dynamic is accompanied by increases in arterial load and load-related concentric LV remodeling in an isolated abdominal obesity cohort. This remodeling could have a significant impact on cardiovascular risk.